Analysis Laboratory Culinary Art At SMK N 3 Solok - Fadhillah, Syahidah Nur; Yelfi, Reno (Universitas Negeri Padang, 2023)
This study aims to describe (1) the condition of the laboratory room area, lighting, floors, walls in the pastry and bakery product practice laboratory (2) describe the effectiveness of practical learning in the pastry and bakery product subject for class 12 at SMK N 3 Kota Solok. This study uses a qualitative descriptive research method, namely research that describes the condition of an object, symptoms and events that are actually appropriate in the field. The research sources were 1 head of workforce, 1 PBB subject teacher, 1 student and 1 alumni of SMK N 3 Solok City. Data collection techniques used are observation, observation, interviews, and documentation. Data analysis techniques use descriptive qualitative, thus this study aims to describe, summarize situations, conditions and various phenomena that exist in reality. The results of the study show that: (1) The review of the area of the room is not in accordance with the standard, namely 72 m2 so that the area of the student's work area is 2 m2/student. (2) seen from the arrangement of seacra equipment and materials that have not been carried out optimally. So it is necessary to make a proposal to develop a laboratory so that it meets standards in accordance with applicable regulations, both in terms of facilities, building materials and equipment, in order to create safety and comfort in the practice process.